ANALISA PERGESERAN MAGNETIC DOMAIN WALL PADA LAPISAN TIPIS FREE LAYER CoFeB UNTUK SISTEM SPIN-VALVE TUNNELING MAGNETO RESISTANCE (TMR) - , GALIH SETYAWAN, Dr. Edi Suharyadi. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Analysis of propagation of magnetic domain wall in a free layer CoFeB thin film have been investigated. The analysis has been done by using micromagnetic simulation software Object Oriented Micromagnetic Framework (OOMMF) based on Landau-Lifshitz Gilbert (LLG). The main purpose of this study is to observe of hysteresis loop, coercivity field, energy ferromagnetic (total energy, exchange energy, demagnetization energy) and Swithing Field Distribution (SFD) analysis with various dimention (size) and thickness of free layer CoFeB thin films. This study have been done with variation size of 120Ã100 nm2, 140Ã100 nm2 and 160Ã100 nm 2. Variation of thickness is 1, 2 and 4 nm. Simulation have been done by applying external magnetic field of 300 Oe in the x direction with 150 steps. The result of size variation simulation for 120Ã100 nm2, 140Ã100 nm2 and 160Ã100 nm 2 with maximum external field 300 Oe have a magnetization of 0.983, 0.985 and 0.988, respectively. At the thickness variation, CoFeB with 1 nm have fast magnetization than others. Magnetization value for variation thickness of 1, 2 and 4 nm at maximum external field of 300 Oe are 0.999, 0.983 and 0.932, respectevely. Several investigations such as energy ferromagnetic system (total energy, exchange energy, demagnetization energy) and switching field distribution (SFD) have been also investigated. Switching field value for variation size of 120Ã100 nm2, 140Ã100 nm2 and 160Ã100 nm 2 are 798 Oe, 920 Oe and 652 Oe, respectively. Switching field value for variation thickness of 1,2 and 4 nm are 192 Oe, 798 Oe and 1182 Oe, respectively.